Blunt traumatic brachial plexus injuries in a northern rural US setting: increased likelihood in unshielded motor-powered crashes. Issue 1 (26th November 2020) - Leonard, Samantha; Woehrle, Theo; Nikizad, Hooman; Vearrier, Jared; Odean, Marilyn; Renier, Colleen; Bollins, John; Eyer, Steven
Abstract : Background: Blunt traumatic brachial plexus injuries (BTBPI) are severe peripheral nerve injuries which present in a small portion of trauma patients but can result in long-term neurological disability and severe chronic pain. Objective: The goal of this study was to describe the epidemiology of BTBPI in a northern rural setting caused by motor-powered collisions, and to determine the relative risk of these injuries in shielded (cars, trucks, vans, and so on) and unshielded vehicles (snowmobiles, all-terrain vehicles and motorcycles). Methods: This retrospective study describes the epidemiology of BTBPI caused by motor-powered collisions and treated at two level II trauma centers in northeast Minnesota and determines the relative risk of these injuries in shielded (cars, trucks, vans, and so on) and unshielded vehicles (snowmobiles, all-terrain vehicles and motorcycles). We hypothesized unshielded motor vehicle crashes in rural areas are at an increased risk of incurring BTBPI. Results: Out of all injuries resulting from motor-powered collisions in a 20-year period (9951), BTBPIs were found in 63 trauma patients, a prevalence of 0.6%. The rate of BTBPI involving unshielded vehicles (1.0%) was significantly higher than those involving a shielded vehicle (0.4%) and primarily occurred in rural areas (70%). Conclusions: Unshielded vehicle crashes, particularly snowmobiles, have the highest risk for BTBPI in our rural region. The overall incidence of these injuries appears to be declining. Level of evidence: Level III.